A Sparkle in Her Eyes - Uran, Rudi (Slovenia, 2014)
A documentary "A sparkle in her eyes" is a portrait of Barbara, a twelve year old girl, who, because of a cerebral palsy -- tetra - pharesis, is "confined" into her own body. In addition, the girl can not speak and her only communication with the world around her is enabled by a "communicator", a little screen which reacts to her eye contact. Barbara emits the extraordinary energy which enchantes everyone who takes time for her. The camera follows her learning process and understanding of everything what she was deprived of before it was established that she was smart and the communicator was supplied.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films